RESTORATIVE LEGAL PROTECTION FOR VICTIMS OF PALM OIL FRUIT THEFT: A CASE STUDY IN THE JURISDICTION OF THE BANGUN PURBA POLICE SECTOR - Dewi Kentri Saragih; Zaid Alfauza Marpaung (Program Pascasarjana UIN Sumatera Utara, 2026)
The theft of oil palm fruit is a criminal offense that frequently occurs in plantation areas and causes losses to victims, both in terms of economic harm and psychological impact. Along with the development of the criminal justice system, the settlement of criminal cases is no longer solely focused on imposing sanctions on offenders but also emphasizes the restoration of victims’ rights and interests through a restorative justice approach. This study aims to examine the forms of restorative protection provided to victims of oil palm fruit theft and to identify the various obstacles encountered in its implementation within the jurisdiction of the Bangun Purba Sector Police. This study employed an empirical legal research method with a qualitative approach. The research data were obtained through interviews with police officers, victims, and other relevant parties, supported by an analysis of applicable laws and regulations and relevant literature. The findings indicate that restorative protection for victims is implemented through mediation between offenders and victims, the provision of compensation or restitution, formal apologies, and the settlement of cases through peaceful agreements facilitated by the police.